Effect of Ce dopant on structure, morphology, photoabsorbance and photocatalysis of ZnWO4nanostructure - Anukorn Phuruangrat (2018)
© 2017 The Ceramic Society of Japan. The effect of Ce dopant on phase, morphology, optical property and photocatalytic activity of ZnWO4was investigated in this research. The products were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and UVvisible spectroscopy. The results showed that the pure product was monoclinic ZnWO4nanorods with the growth direction of [021] and that Ce3+ and W6+ ions contained in the Ce-doped products. The photocatalytic activities of the photocatalysts were evaluated through the degradation of methylene blue (MB) solutions under UV-light illumination. The results showed that the efficiencies for MB photocatalytic degradation were influenced by Ce dopant. The photocatalytic activities of the Ce-doped ZnWO4samples were higher than that of the pure ZnWO4.